1999
DOI: 10.1074/jbc.274.49.34785
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Ligand Binding Domains in Chimeric Fibroblast Growth Factor Receptor Molecules

Abstract: Fibroblast growth factors (FGFs) 1 are essential signaling molecules that regulate embryonic growth, development, cell proliferation, differentiation, and angiogenesis (1). At least 19 related members of the FGF family have been identified thus far, and all but four are known to activate one of four high affinity cell surface FGF receptors (FGFR) (2-9).2 The FGFRs consist of an extracellular region containing three immunoglobulin-like (Ig) domains, a stretch of seven conserved acidic amino acids, and a hepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 58 publications
(30 reference statements)
3
63
1
Order By: Relevance
“…FGFs elicit their biological activities by binding to high a nity FGF receptor (FGFR) tyrosine kinases in the presence of heparin or heparan sulfate. There are four FGFRs (FGFR1 ± 4), with multiple additional isoforms due to alternative mRNA splicing, but only FGFR1 and FGFR2 isoforms appear to have high a nity for FGF-2 (Chellaiah et al, 1994;Mansukhani et al, 1992;Ornitz et al, 1996;Ron et al, 1993;Werner et al, 1992). FGFR1 has often been used as a model to understand the activation of FGFRs as well as the early signalling events induced by FGF-2.…”
Section: Introductionmentioning
confidence: 99%
“…FGFs elicit their biological activities by binding to high a nity FGF receptor (FGFR) tyrosine kinases in the presence of heparin or heparan sulfate. There are four FGFRs (FGFR1 ± 4), with multiple additional isoforms due to alternative mRNA splicing, but only FGFR1 and FGFR2 isoforms appear to have high a nity for FGF-2 (Chellaiah et al, 1994;Mansukhani et al, 1992;Ornitz et al, 1996;Ron et al, 1993;Werner et al, 1992). FGFR1 has often been used as a model to understand the activation of FGFRs as well as the early signalling events induced by FGF-2.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, FGFR1 may confer a selectable advantage on clones of cells in colorectal tumorigenesis, favoring proliferation, whereas FGFR3 may have the effect of an unfavorable negative regulation of progression of the carcinomas to malignancy, probably promoting differentiation. In support, several studies using BaF3 cells system have indicated that FGFR1 is much better at producing mitogenic signals than FGFR3 (Chellaiah et al, 1994;Wang et al, 1994;Ornitz et al, 1996).…”
mentioning
confidence: 87%
“…One kind of splice variant involves the use of alternative exons encoding the carboxyl-terminal half of the third immunoglobulin domain. This form of splice variation occurs for FGFR1, FGFR2 and FGFR3 so that IIIb and IIIc forms of these receptors have very di erent ligand binding properties (Miki et al, 1992;Werner et al, 1992;Chellaiah et al, 1994). These two isoforms appear to be expressed in a mutually exclusive fashion with cells of mesenchymal origin expressing IIIc variants of FGFR2 and FGFR3 whereas epithelial cells express the IIIb isoform (Pekonen et al, 1993;Savagner et al, 1994).…”
Section: Introductionmentioning
confidence: 99%